A continuum model of nanocrystalline metals under shock loading - Jérusalem, A; Radovitzky, R (2009)
Recent atomistic simulations have shown that grain boundary sliding in nanocrystals is altered under shock loading conditions. It is found that the high state of compression inhibits grain boundary sliding and reactivates intragrain dislocation activity. This leads to higher material strength and postpones the transition between these two deformation mechanisms to smaller grain size. We present here a continuum model aimed at extending the model proposed by Jérusalem et al for quasi-static and high rates (2007 Phil. Mag. 87 2541-59) to shock loading. To this end, the shock response of nanocrystals is investigated by accounting specifically for additional frictional deformation-inhibiting effects. The model is based on a numerical finite element discretization of the polycrystal, considered as a continuum, with embedded surfaces of discontinuity accounting for the grain boundary response. Interface elements are formulated to account for the special kinematics of grain boundaries, i.e. to describe grain boundary frictional sliding and other accommodation mechanisms. The response of grain interiors is modeled with a high rate equation of state for the volumetric response and a simple plasticity model to describe their deviatoric response. A large-scale parallel computing framework is finally developed to calibrate and investigate the specificities of the deformation mechanisms under shock loading conditions, and the results are compared in detail with atomistic results. As a conclusion, this extended three-dimensional continuum model constitutes a promising first step for the characterization of large-scale nanocrystalline deformation under the most complete range of loading rates yet proposed in continuum simulations, namely, from quasi-static to shock loading. © 2009 IOP Publishing Ltd.